DETERMINANTS OF THE EXCHANGE RATE OF THE RUPIAH TO THE AMERICAN DOLLAR AFTER THE CRISIS 2008 - Dwita Sakuntala; July Meliza (Quantitative Economics Journal, 2022)
AbstractAfter the financial crisis that hit America at the end of 2008, many countries were affected by the decline in the country's economic conditions. This is because America is a country that has large funds that are widely used in several developing countries in the form of portfolio investment and direct investments. As a result of the weakening of the US economy, many foreign investors are attracting investment portfolio funds to strengthen the company's capital in their home countries. So that there was a capital outflow. In Indonesia, one of the indicators that can be seen from the consequences of this crisis is the weakening exchange rate. This article aims to describe the research results of factors that affect the rupiah exchange rate over the US dollar after the crisis with the study period Q1.2010 - Q4.2016. ARCH / GARCH is used to form a variable model that has very high volatility in a period and in other periods the volatility is very low. The empirical result shows that the best model is the GARCH (1,1) model with variance regressors is inflation. The variable which has positive and significant influence is the variable of the money supply, and interest rates. Real GDP has a negative and significant influence on the exchange rate. ARCH/GARCH variable is significant. But the inflation variable and regression variant of inflation are not significant. The variable which has positive and significant influence is the variable of the money supply, and interest rates. Real GDP has a negative and significant influence on the exchange rate. ARCH/GARCH variable is significant. But the inflation variable and regression variant of inflation are not significant. The variable which has positive and significant influence is the variable of the money supply, and interest rates. Real GDP has a negative and significant influence on the exchange rate. ARCH/GARCH variable is significant. But the inflation variable and regression variant of inflation are not significant.Thisthe model is passed the classical assumption test.This research model has a higher R2 value than other models.